Find all triples of positive integers (x,y,z) such that

$x^{z+1} \ - \ y^{z+1}=2^{100}$

The RHS is even, then x and y must be odd and $x^{z+1}>y^{z+1}$, but how to find out them all ?

  • $\begingroup$ are $x,y$ positive or not necessarily? $\endgroup$
    – N. S.
    Dec 2, 2013 at 1:59
  • $\begingroup$ They are positive, let me edit it ! $\endgroup$
    – Joel
    Dec 2, 2013 at 2:01
  • $\begingroup$ The case $z=2$ is easy, while for $z=3, z=4, z=9, z=24, z=49$ and $z=99$ there is no solution by FLT. The case $z=6$ is a particular case of $z=2$. $\endgroup$
    – N. S.
    Dec 2, 2013 at 2:41
  • $\begingroup$ also if $z+2$ is prime, there is no solution. Actually if $p \neq 2$ is a prime so that $p-1|z+1$, there is no solution. This takes care of many odd $z's$. $\endgroup$
    – N. S.
    Dec 2, 2013 at 2:43

2 Answers 2


You can factor $x^{z+1}-y^{z+1}$ by dividing out $x-y$. This shows that $x-y$ is a power of $2.$ But they must only have the same parity-they can both be even. In particular, there are many solutions with $z=0$ If $z=1$ you can factor it as $(x-y)(x+y)=2^{100}$ and you can find a finite number of solutions here. I think, but have not proved, that you will not find any with larger $z$.


$x \ge 0 \land y \ge 0 \rightarrow x \ge y$.

$$x^{z+1} - y^{z+1} = \left(x - y\right)\left(x^z + x^{z-1}y + x^{z-2}y^2 + \dots +y^z\right) = 2^{k+1} \tag{T1}$$

So we can conclude $x - y = 2^{r_1}$, and that $x$ and $y$ have the same parity.

If $z$ is even, rewrite $(T1)$:

$$x^z + y^z + xy\underbrace{\left(x^{z-2} + x^{z-3}y + \dots + y^{z-2}\right)}_{\text{An odd number of terms}} = 2^{k} \tag{T2}$$

Since $x$ and $y$ have the same parity then $x$ and $y$ must both be even to satisfy the parity of $(T2)$. Let $2a = x$ and $2b = y$.

$$a^{z+1} - b^{z+1} = 2^{k - z}$$

which is a smaller instance of the original problem with the added assumption that $z$ is even. We can repeat the proof to get either $\exists c\, d\, : 2c = a \land 2d = b$ or that $2^{k - \dots}$ is no longer an integer, ad nauseam.

If $z$ is odd,

$$x^{z+1} - y^{z+1} = \left(x + y\right)\left(x^z - x^{z-1}y + x^{z-2}y^2 - \dots -y^z\right) = 2^{k}$$

Conclude odd $z$ leaves a system of equations $$x-y = 2^{r_1}$$ $$x+y = 2^{r_2}$$

$x = 2^{r_2 -1} + 2^{r_1 - 1}, y = 2^{r_2 -1} - 2^{r_1 - 1}$

Expanding $x^{z+1} - y^{z+1} = 2^{k+1}$ for $z=1$ gives a set of solutions: $$2^{r_1 + r_2} = 2^{k+1}$$ $$(x,y,z) \in (2^{n - 1} + 2^{k - n},2^{n - 1} - 2^{k - n},1)\, 1 \le n \le k$$

Expanding for $z = 3$ gives another set:

$$2^{3r_2 + r_1 - 1} + 2^{3r_1 + r_2 - 1} = 2^{k+1}$$

with $(x,y,z)$ being found by the $r_1$ and $r_2$ values that satisfy the above.

At this point I'm unsure how to continue. All further expansions $z > 3$ seem to involve only positive terms, some of the form $A\cdot 2^{B(r_1, r_2)}\, ,\, A \ne 2$, which comes from the binomial expansion. It might be provable by induction. If so, then there are no more solutions.

  • 2
    $\begingroup$ $x - y$ is a power of $2$, but why do you think it is $2$? For example, with $z=1$ you could have $x= 2^{97}+2$, $y = 2^{97} - 2$. $\endgroup$ Dec 2, 2013 at 2:40
  • $\begingroup$ You are obviously correct, I don't know what I was thinking. Let me try to fix that... $\endgroup$
    – DanielV
    Dec 2, 2013 at 3:41

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.